Diamine Fungal Inducers of Secondary Metabolism: 1,3-Diaminopropane and Spermidine Trigger Enzymes Involved in β-Alanine and Pantothenic Acid Biosynthesis, Precursors of Phosphopantetheine in the Activation of Multidomain Enzymes - Juan Francisco Martín; Paloma Liras (MDPI AG, 2024)
The biosynthesis of antibiotics and other secondary metabolites (also named special metabolites) is regulated by multiple regulatory networks and cascades that act by binding transcriptional factors to the promoter regions of different biosynthetic gene clusters. The binding affinity of transcriptional factors is frequently modulated by their interaction with specific ligand molecules. In the last decades, it was found that the biosynthesis of penicillin is induced by two different molecules, 1,3-diaminopropane and spermidine, but not by putrescine (1,4-diaminobutane) or spermine. 1,3-diaminopropane and spermidine induce the expression of penicillin biosynthetic genes in Penicillium chrysogenum. Proteomic studies clearly identified two different proteins that respond to the addition to cultures of these inducers and are involved in β-alanine and pantothenic acid biosynthesis. These compounds are intermediates in the biosynthesis of phosphopantetheine that is required for the activation of non-ribosomal peptide synthetases, polyketide synthases, and fatty acid synthases. These large-size multidomain enzymes are inactive in the "apo" form and are activated by covalent addition of the phosphopantetheine prosthetic group by phosphopantetheinyl transferases. Both 1,3-diaminopropane and spermidine have a similar effect on the biosynthesis of cephalosporin by Acremonium chrysogenum and lovastatin by Aspergillus terreus, suggesting that this is a common regulatory mechanism in the biosynthesis of bioactive secondary metabolites/natural products.